Ketahanan Pangan Rumah Tangga Peternak Sapi Potong Rakyat di Daerah Istimewa Yogyakarta, Indonesia - Ferdian Achmad; Jangkung Handoyo Mulyo; Masyhuri Masyhuri; Subejo Subejo (Jurnal Ketahanan Nasional, 2019)
ABSTRACT One of the determinants of the national resilience of a nation was food security. The food consumption sector had a very vital and strategic role in every country. This study aimed to knew and to compared the degree of food  security  between the households of beef cattle farmersunder the self-ownership  and the partnership systems in the Special Region of Yogyakarta province. The number of samples studied were as many as 240 beef cattle farmers, consisting of 120 self-ownership system farmers, and 120 partnership system farmers. The primary method of research using a quantitative approach that was descriptive analysis. An instrument of measuring used was cross-classification between the share of food expenditure (PPP) and energy sufficiency (AKE) which was measured using an indicator of Jonsson and Toole’s table (1991).The results showed that the household food security of beef cattle farmersself-ownership system was better than partnership system farmers. The level of food security of livestock households in DI Yogyakarta in aggregates were 17.92% food secure, 17.08% food vulnerable, 39.17% food less secure, and 25.83% food insecure. Based on the system of livestock ownership, households of self-ownership system farmers were 22.5% food secure, 15.83%   were food vulnerable, 40.00% food less secure, and 21.67% were food insecure. In partnership farmers, 13.33% food secure, 18.ABSTRAKSalah satu faktor penentu ketahanan nasional suatu bangsa adalah ketahanan pangan.Sektor konsumsi pangan memiliki peran yang sangat vital dan strategis pada setiap negara.Tujuan penelitian ini adalah untuk mengetahui dan membandingkan derajat ketahanan pangan rumah tangga peternak sapi potong antara sistem mandiri dan sistem gaduhan di DI Yogyakarta.Sampel yang diteliti  sebanyak 240 orang peternak sapi potong, terdiri dari 120 orang peternak sistem mandiri, dan 120 orang peternak sistem gaduhan. Metode dasar penelitian menggunakan pendekatan kuantitatif yang bersifat deskriptif analisis. Instrumen alat ukur yang digunakan yaitu klasifikasi silang antara pangsa pengeluaran pangan (PPP) dan angka kecukupan energi (AKE) yang diukur menggunakan indikator Tabel Jonsson dan Toole (1991).Hasil penelitian menunjukkan bahwa ketahanan pangan rumah tangga peternak sapi potong sistem mandiri lebih baik dibandingkan peternak sistem gaduhan. Derajat ketahanan pangan rumah tangga ternak di DI Yogyakarta secara agregat berturut-turut yaitu sebanyak 17,92% tahan pangan, 17,08% rentan pangan, 39,17% kurang pangan, dan 25,83% rawan pangan. Berdasarkan sistem kepemilikan ternak, rumah tangga peternak sistem mandiri sebanyak 22,5% tahan pangan, 15,83% rentan pangan, 40,00% kurang pangan, dan 21,67% termasuk rawan pangan. Pada peternak sistem gaduhan, sebanyak 13,33% termasuk rumah tangga tahan pangan, 18,33% rentan pangan, 38,34% kurang pangan, dan 30,00% rawan pangan..